Comparaison de trois index de qualité de l'huître creuse Crassostrea gigas - Berthome, Jean-paul; Deslous-paoli, Jean-marc; Fernandez-castro, N. (ICES Symposium, Woods Hole, MA (USA), 2 Apr 1979, 1979)
Three indexes of quality of Japanese oyster Crassostrea gigas were studied in 3 lots of oysters bred in the r.1arennes-oléron basin from february to july 1979: condition index of MEDCOF &-. NEEDLER, thickness coefficient of IMAI & SAKAI and external quality coefficient of BERTHOME. These different indexes were correlated within each lot of oysters. The external quality coefficient is always significantly correlated with condition index, while thickness coefficient is correlated with other two only for one lot, but seemes useful to rate oyster growth better. Trois index de qualité de l'huître creuse Crassostrea gigas ont été étudiés sur 3 lots d'huîtres élevées dans le bassin de Marennes Oléron de février à juillet 1979: L'index de condition de MEDCOF et NEEDLER, le coefficient d'épaisseur d' IMAI et SAKAI et le coefficient de qualité externe de BERTHOME. Ces différents index ont été corrélés entre eux pour chaque lot d'huître. Le coefficient de qualité externe est toujours corrélé significativement avec l'index de condition alors que le coefficient d'épaisseur n'est corrélé avec lès deux autres que pour un seul lot mais semble utile pour mieux appréhender la croissance des huîtres.